Triphasic partitioning of mixed Scenedesmus and Desmodesmus for nutrients extraction and chlorophyll composition prediction for algae bloom - Tang D.Y.Y.; Chew K.W.; Chia S.R.; Ting H.-Y.; Sia Y.-H.; Gentili F.G.; Ma Z.; Awasthi M.K.; Show P.L. (Taylor and Francis Ltd., 2023)
Acetone; Antioxidants; Aquatic ecosystems; Chlorophyll; Fatty acids; Microorganisms; Polysaccharides; Proteins; Regression analysis; Algae blooms; Chlorophyll concentration; Ecosystem health; Extractants; Harmful algae; Micro-algae; Nutrient extraction; Red green blues; Scenedesmus; Tri-Phasic; Microalgae